2018
DOI: 10.3346/jkms.2018.33.e169
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Pneumonia Severity and Pulmonary Complications in Middle East Respiratory Syndrome

Abstract: This nationwide, prospective cohort study evaluated pulmonary function and radiological sequelae according to infection severity in 73 survivors from the 2015 Middle East respiratory syndrome (MERS) outbreak in Korea. Patients with severe pneumonia in MERS-coronavirus infection had more impaired pulmonary function than those with no or mild pneumonia at the 1-year follow-up, which was compatible with the radiological sequelae. Severe pneumonia significantly impairs pulmonary function and makes long radiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
85
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 16 publications
11
85
0
3
Order By: Relevance
“…In this regard, elevated C-reactive protein may be predictive of radiological sequelae. Prior studies indicated that radiological sequelae from SARS and MERS may suggest the abnormal or repaired lung function (30,32). Despite the slight residuals in COVID-19, a long-term follow-up is required to further trace the resolution and associations with lung function.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, elevated C-reactive protein may be predictive of radiological sequelae. Prior studies indicated that radiological sequelae from SARS and MERS may suggest the abnormal or repaired lung function (30,32). Despite the slight residuals in COVID-19, a long-term follow-up is required to further trace the resolution and associations with lung function.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report portrayed that discharged patients with COVID-19 pneumonia are still having residual abnormalities in chest CT scans, with ground-glass opacity as the most common pattern 4 . Persistent impairment of pulmonary function and exercise capacity have been known to last for months or even years [5][6][7][8] in the recovered survivors with other coronavirus pneumonia (severe acute respiratory syndrome/SARS and middle east respiratory syndrome/MERS). However, until now, there is no report in regard to pulmonary function in discharged COVID-19 survivors.…”
Section: To the Editorsmentioning
confidence: 99%
“…Post-acute early rehabilitation of coronavirus survivors would foremost involve recovery of body structure and function. Impairment of respiratory function [9][10][11], exercise tolerance [12] and neuromuscular functions [13] have been reported to be present in coronavirus survivors beyond 3 months post-infection, with improvement to some degree in many of these individuals. However, improvement in these impairments of body structure and function may not necessarily translate into recovery from disability and role limitation [14,15].…”
Section: Introductionmentioning
confidence: 99%